Held back and pushed forward: leading change in a complex public sector environment. Issue 2 (13th April 2015) - van der Voet, Joris; Kuipers, Ben; Groeneveld, Sandra
Abstract : Purpose: – Public organizations often need to implement organizational change. Several authors have argued that the specific characteristics of public organizations make the implementation of organizational change in public organizations distinct or even more difficult. However, this issue has received little empirical investigation in both public management and change management research. Public organizations typically operate in an environment characterized by checks and balances, shared power, divergent interests and the political primate. The purpose of this paper is to advance knowledge about how the implementation of change and its leadership is affected by the complex environment in which public organizations operate. Design/methodology/approach: – A case study approach is adopted. A merger of three government departments in a Dutch city is selected as a case. This merger took place in an environment that became increasingly complex as the implementation process advanced. The main method of data collection was interviewing the managers that were involved in the organizational change. In all, 23 interviews were conducted and fully transcribed. The interviews were then coded using Atlas.ti software. Findings: – The analysis indicates that a high degree of environmental complexity forces public organizations to adopt a planned, top-down approach to change, while the effectiveness of such an approach to change is simultaneously limited by a complex environment. In addition, typical change leadership activities, such as defining the need for change, role modeling and motivating employees to implement the change, are not sufficient to implement change in a complex environment. In order to overcome environmental dependencies and maintain momentum in the change process, public managers must engage in more externally oriented leadership activities. Originality/value: – The paper provides empirical evidence about the relevant and rapidly growing research topic of organizational change in public organizations. The paper concludes with hypotheses that can be tested in follow-up research, and as such provides a starting point for future research concerning change management in public organizations.